Developing a Smart Village Model to Support Food Security Programs in Rural Villages of Gempol Subdistrict, Pasuruan Regency - Khumaidi (International Publisher, 2025)
This study aimed to develop a Smart Village model to enhance food security in rural villages of Gempol Subdistrict, Pasuruan Regency, Indonesia. Employing a qualitative research approach, the study utilized a systematic literature review and field observations to gather data. The population comprised residents of Gempol Subdistrict, with a purposive sample of 50 individuals, including local government officials, farmers, and community leaders. Data collection instruments included semi-structured interviews, focus group discussions, and document analysis. The findings revealed that integrating Information and Communication Technology (ICT) into village governance, agriculture, and community empowerment significantly contributes to food security. Key components of the proposed Smart Village model encompass smart governance through digital administrative systems, smart agriculture via precision farming technologies, and community empowerment through digital literacy programs. The implementation of this model is anticipated to improve agricultural productivity, streamline distribution channels, and foster active community participation. The study concludes that a tailored Smart Village model, responsive to local needs and potentials, can effectively support food security initiatives in rural Indonesian contexts.